FGTeeV: Out of time! - Book 4 - FGTeeV; Diaz Rivas, Miguel (New York, NY, USA : Harper Alley, an imprint of Harper Collins, 2023)
"The FGTeeV family gamers have survived their fair share of glitchy gaming consoles and weird goings-on. But when Duddz can't stop gaming on his fancy new eWatch, the whole family winds up sucked into the watch and on a perilous adventure across space and time!"--
Keywords: Video gamers -- Comic books, strips, etc; Video games -- Comic books, strips, etc; Rescues -- Comic books, strips, etc; Families -- Comic books, strips, etc; Imaginary wars and battles -- Comic books, strips, etc; Video gamers -- Fiction; Video games -- Fiction; Rescues -- Fiction; Families -- Fiction; Imaginary wars and battles -- Fiction; Fantasy gamers -- Fiction; Fantasy comics; Graphic novels; Comics (Graphic works)